Obtaining normal flexion and extension of knee joints on supine, prone and standing positions in osteoarthritis by topical phyto-therapeutic treatment irrespective of age and sex - Apurba Ganguly, (International Journal of Phytomedicine, 2015)
Osteoarthritis (OA) is not a simply process of wear and tear, but an abnormal remodeling of joint tissues driven by a host of inflammatory mediators, including disorders of specific nerves within the affected joint. The common risk factor of OA includes age, sex, prior joint injury, obesity, genetic predisposition and mechanical factor, including malalignment and abnormal joint shape. This paper reports for the first time that normal flexion and extension of knee joints on supine, prone and standing positions in osteoarthritis by topical phytotherapeutic treatment can be achieved, with sustenance, irrespective of age and sex.